Bacterial Profile of External Ocular Infections, Its Associated Factors, and Antimicrobial Susceptibility Pattern among Patients Attending Karamara Hospital, Jigjiga, Eastern Ethiopia - Abebe, Tigist; Teklemariam, Zelalem; Shume, Tadesse; Mekuria, Surafel; Urgesa, Kedir; Weldegebreal, Fitsum (International Journal of Microbiology, 2023)
Background. External ocular infection is a global public health problem. Frequently, bacteria cause an ocular infection that ranges from morbidity to loss of vision. The increasing bacterial resistance in ocular infections leads to the risk of treatment failure with possibly serious consequences. Objective. The study aimed to assess the bacterial profile of external ocular infections, their associated factors, and antimicrobial susceptibility pattern among patients admitted to Karamara hospital, Jigjiga, Eastern Ethiopia. Method. Institutional-basedcross-sectional study was conducted on 288 conveniently selected patients among patients admitted to Karamara hospital from May 1 to June 30, 2020. Data were collected using a structured questionnaire. The ocular sample was collected and cultured in the appropriate culture media and identified using a series of biochemical tests. Antimicrobial susceptibility testing of isolates was performed by using the disk diffusion method. Data were double entered onto EpiData version 3.1 then exported to SPSS version 20 and analyzed to calculate descriptive frequency and odds ratio, and p value ≤0.05 was taken as the significant value. Result. The prevalence of bacterial infection in external ocular samples was 62.2% (95% CI: 56.6%, 68.4%). Out of the 179 isolates, the majority of the bacterial isolates (87.7%) were Gram-positive. Staphylococcus aureus (53.1%) was the predominant isolate. Using soap for washing the face (AOR = 0.43; 95% CI: 0.29, 0.95), having diabetes mellitus (AOR = 3.11; 95% CI: 1.45, 6.75), and history of hospitalization (AOR = 2.82; 95% CI: 1.44, 5.54) were significantly associated with external ocular infection. Most (95.5%) of the Gram-positive bacteria showed resistance to penicillin, but they were susceptible to vancomycin, clindamycin, and ciprofloxacin. Conclusion. The study showed a high prevalence of bacterial infections with the predominant isolate was S. aureus. Penicillin-resistant bacteria were identified among Gram-positive bacterial isolates. Soap usage, hospitalization, and diabetes mellitus were associated with the infection. Antibiotics that were susceptible to the specific bacteria should be used as a drug of choice and using soap for washing the face is advisable to protect against external ocular infection.